Intestinal fatty acid-binding protein (I-FABP) at ICU admission as early biomarker of intestinal injury and predictor of mortality in septic shock - Thorben Pape; Pedro David Wendel-Garcia; Nina Rittgerodt; Bahar Nalbant; Jan Hinrichs; Lena S. Becker; Anna M. Hunkemöller; Jakob Raith; Sören K. J. Boblitz; Jannik Ruwisch; Pia-Victoria Fangmann; Heiner Wedemeyer; et al. (Intensive Care Medicine Experimental, 2026)
Abstract Background Septic shock and acute respiratory distress syndrome (ARDS) are major causes of mortality. Intestinal hypoperfusion is a frequent but often unrecognized complication, and the timing and extent of intestinal injury in these syndromes remain unclear. Intestinal fatty acid-binding protein (I-FABP) has emerged as a potential biomarker of intestinal injury. This study aimed to define a clinically relevant I-FABP cutoff for predicting relevant intestinal injury and to assess its association with disease severity and outcome. Methods We performed a post-hoc analysis combining cohorts of critically ill patients from the prospective EXCHANGE-pilot, the RCT EXCHANGE-1, and the SPARE-14 registry. The analysis included 102 patients with septic shock and/or ARDS, 22 patients with non-occlusive mesenteric ischemia (NOMI) from the REPERFUSE study, and 20 healthy individuals. Circulating I-FABP concentrations were measured by ELISA in plasma samples obtained at ICU admission. Receiver operating characteristic (ROC) analysis was used to define the optimal I-FABP threshold for predicting intestinal hypoperfusion, using patients with NOMI as positive- and healthy individuals as negative controls. Associations between I-FABP, disease severity, and 28-day mortality were analyzed. Results ROC analysis identified an initial I-FABP cutoff of 1070 pg/ml (sensitivity 68%, specificity 100%) for the development of intestinal ischemia defined by criteria of manifest NOMI. I-FABP levels at ICU admission were significantly elevated in patients with ARDS and/or septic shock compared with healthy controls (1108 pg/ml (IQR 291–2846) vs. 479 pg/ml (IQR 358–631), p = 0.03), and comparable to those in NOMI patients. Exploratory generalized additive model analyses indicated a non-linear association between I-FABP concentrations and established markers of shock severity. Patients with high I-FABP levels (above 1070 pg/ml) had a higher 28-day mortality (high: 52.9% vs. low: 33.3%, p = 0.02). In a multivariate logistic regression model, I-FABP and SOFA score remained independently associated with 28-day mortality (I-FABP: adjusted OR 1.27 (1.03–1.62), p = 0.023), without independent association of lactate concentration. Conclusion Elevated plasma I-FABP may identify undetected intestinal injury in critically ill patients with septic shock and/or ARDS and might be associated with higher 28-day mortality. Additionally, I-FABP might reflect a distinct facet of critical illness that is not fully captured by conventional measures of organ dysfunction or shock severity and I-FABP concentrations ≥ 1070 pg/ml may help identify patients at high risk for intestinal ischemia who could benefit from early therapeutic interventions.